2009
DOI: 10.1182/blood-2008-08-173658
|View full text |Cite
|
Sign up to set email alerts
|

Murine neonatal recent thymic emigrants are phenotypically and functionally distinct from adult recent thymic emigrants

Abstract: In contrast to adults, the murine neonatal CD4 ؉ compartment contains a high frequency of recent thymic emigrants (RTEs). However, the functional capabilities of these cells in neonates are relatively unknown. Moreover, it has not been determined whether RTEs from neonates and adults are comparable. Here we have directly compared neonatal and adult CD4 ؉ RTEs for the first time, using a transgenic mouse strain that allows for the identification and purification of RTEs.Our data demonstrate that RTEs from murin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 47 publications
1
79
0
Order By: Relevance
“…RTEs constitute the entire T-cell pool in neonates, seeding the lymphopenic peripheral compartment to establish the nascent immune system. [1][2][3] In adults recovering from lymphopenia, such as after bone marrow transplantation or a lymphodepleting viral infection, RTEs play an essential role in reconstituting the naive T-cell pool. Despite age-associated thymic involution, the reduced export of RTEs adds new T-cell receptor (TCR) specificities to the peripheral T-cell pool, although their contribution declines with age.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RTEs constitute the entire T-cell pool in neonates, seeding the lymphopenic peripheral compartment to establish the nascent immune system. [1][2][3] In adults recovering from lymphopenia, such as after bone marrow transplantation or a lymphodepleting viral infection, RTEs play an essential role in reconstituting the naive T-cell pool. Despite age-associated thymic involution, the reduced export of RTEs adds new T-cell receptor (TCR) specificities to the peripheral T-cell pool, although their contribution declines with age.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both rodents and humans have shown that the completion of T-cell maturation requires both exit from the thymus and access to secondary lymphoid organs and is marked by changes in cell-surface phenotype and function. 3,[6][7][8][9][10][11] Given that analyses of the more tractable mouse models are highly likely to be predictive of human biology, the study of RTEs has been facilitated by the use of mice transgenic (Tg) for green fluorescent protein (GFP) driven by the Rag2 promoter. In such RAG2p-GFP Tg mice, GFP and Rag2 expression are coincident in the late double-negative stage in the thymus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the peripheral T cells in neonates are recent thymic emigrants (RTE), which are defective in developing Th1 responses [13][14][15] and may explain Th2 skewing in some situations. RTE from neonates undergo increased IL-7-dependent proliferation in the periphery compared to RTE in adult mice.…”
Section: Neonatal Adaptive Immunitymentioning
confidence: 99%
“…RTE from neonates undergo increased IL-7-dependent proliferation in the periphery compared to RTE in adult mice. 15 In a co-transfer model of Listeria monocytogenes, neonate and adult transgenic CD8 T cells were allowed to respond to infection within the same inflammatory environment. 16 Neonatal cells were found to proliferate and differentiate faster than adult cells after infection.…”
Section: Neonatal Adaptive Immunitymentioning
confidence: 99%